THE LEADERSHIP OF THE SCHOOL PRINCIPAL IN REALIZING INDEPENDENT LEARNING IN SCHOOLS - Jannaty, Washifah; Islam, Saiful (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Significant changes in the world of Indonesian education occurred with the introduction of the concept of Independent Learning as part of educational reform. This concept emphasizes student independence, increased creativity, and active participation in the learning process. The principal's leadership is key in managing and realizing the concept of Independent Learning at the secondary school level. This research was conducted at SMP Negeri 1 Wringin with the aim of in-depth and analyzing the leadership role of the school principal in realizing the concept of Independent Learning. The research method used is qualitative, with a focus on exploring the dynamics of the principal's leadership, the challenges faced, and the strategies implemented in responding to the concept of Independent Learning in the school. The research results show that the leadership of the school principal has a strategic role in forming a school culture that supports Freedom of Learning. The role of the school principal is not only limited to administrative aspects, but also has a strategic impact in facing technological developments and globalization to prepare students to become independent and creative individuals. This research is expected to contribute to the educational leadership literature, while the results can become a practical guide for school principals, teaching staff, and other stakeholders in achieving the goal of Independent Learning in the school environment.